Selective Attention Measurement of Experienced Simultaneous Interpreters Using EEG Phase-Locked Response - Yagura, Haruko; Tanaka, Hiroki; Kinoshita, Taiki; Watanabe, Hiroki; Motomura, Shunnosuke; Sudoh, Katsuhito; Nakamura, Satoshi (Frontiers in Human Neuroscience, 2021)
We quantified the electroencephalogram signals associated with the selective attention processing of experienced simultaneous interpreters and calculated the phase-locked responses evoked by a 40-Hz auditory steady-state response (40-Hz ASSR) and the values of robust inter-trial coherence (ITC) for environmental changes. Since we assumed that an interpreter's attention ability improves with an increase in the number of years of experience of simultaneous interpretation, we divided the participants into two groups based on their simultaneous interpretation experience: experts with more than 15 years of experience (E group; n = 7) and beginners with <1 year (B group; n = 15). We also compared two conditions: simultaneous interpretation (SI) and shadowing (SH). We found a significant interaction in the ITC between years of SI experience (E and B groups) and tasks (SI and SH). This result demonstrates that the number of years of SI experience influences selective attention during interpretation.